Cognitive mistakes of codependents as a way to protect against uncertainty - Natalia G. Artemtseva; Malkina A. Malkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper is devoted to the problem of studying the inner subjective world of a codependent personality. Despite the active scientific studies of the phenomenon of codependency in recent years, there is still room for new ideas in this area. The problem under study is interesting and relevant both for psychological science in general, and for practical and consulting psychology. The purpose of the study presented in the paper is to identify cognitive mistakes inherent in individuals with actualized codependency. Codependency is considered not only as being close to a dependent relative, but more broadly as a set of certain patterns of thinking and behavioral characteristics. As a result of the study, the severity of certain cognitive errors in codependent subjects was found. Cognitive errors of thinking that are present both in the group of actualized codependents and in the group of non-actualized codependents are revealed. When comparing the indicators of the severity of cognitive errors in codependent men and women, a general trend of the presence of cognitive errors was found: in actualized codependents, the indicators of men and women do not differ, and in non-actualized codependents, almost all cognitive errors are significantly more pronounced than in men. It is shown that cognitive errors aimed at avoiding uncertainty prevail in people with actualized codependency. It is concluded that the cognitive errors identified in codependents are not just associated with a state of uncertainty, but can also be a way to protect against it. The results of the research can be used in the development of therapeutic strategies for correcting the manifestations of codependency through awareness and correction of cognitive mistakes.